Pengaruh Investment Opportunity Set (IOS) Dan Kinerja Keuangan Terhadap Kebijakan Dividen - Munawar, Dimas; Indrawan, I Gede Adi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the effect of Investment Opportunity Set (IOS) and Financial Performance on Dividend Policy. The research method used is quantitative by proposing a hypothesis to be tested. Selection of research samples using purposive sampling method with certain criteria. The population used in the study were companies listed in the consumer non-cyclicals sector on the Indonesia Stock Exchange in 2018-2022. The statistical analysis method used in the research is multiple regression analysis with. The results obtained in this study are that simultaneously IOS, profitability, and leverage affect dividend policy. While partial testing shows the results that only leverage has a significant effect on dividend policy. While IOS and profitability have no effect on dividend policy.